Robust Conservative Level Set Method for 3D Mixed-Element Meshes — Application to LES of Primary Liquid-Sheet Breakup (Communications in Computational Physics, 2014)
In this article we detail the methodology developed to construct an efficientinterface description technique — the robust conservative level set (RCLS) —to simulate multiphase flows on mixed-element unstructured meshes while conservingmass to machine accuracy. The approach is tailored specifically for industry as thethree-dimensional unstructured approach allows for the treatment of very complexgeometries. In addition, special care has been taken to optimise the trade-off betweenaccuracy and computational cost while maintaining the robustness of the numericalmethod. This was achieved by solving the transport equations for the liquid volumefraction using a WENO scheme for polyhedral meshes and by adding a flux-limiteralgorithm. The performance of the resulting method has been compared against establishedmultiphase numerical methods and its ability to capture the physics of multiphaseflows is demonstrated on a range of relevant test cases. Finally, the RCLSmethod has been applied to the simulation of the primary breakup of a flat liquid sheetof kerosene in co-flowing high-pressure gas. This quasi-DNS/LES computation wasperformed at relevant aero-engine conditions on a three-dimensional mixed-elementunstructured mesh. The numerical results have been validated qualitatively againsttheoretical predictions and experimental data. In particular, the expected breakupregime was observed in the simulation results. Finally, the computation reproducedfaithfully the breakup length predicted by a correlation based on experimental data.This constitutes a first step towards a quantitative validation.